Urban landscape resilience: integrating natural areas with urban planning - Ribeiro, Marina (Universidade Federal de São Carlos, 2025)
As urbanization accelerates rapidly, projections indicate that by 2050, four out of every five people will live in cities, underscoring the urgent need to mitigate environmental impacts while promoting sustainable urban development. Cities, responsible for around 70% of global greenhouse gas emissions, are both vulnerable to climate change and essential to addressing it. Recent climate-related disasters, such as floods and heatwaves, exacerbate socioeconomic inequalities, disproportionately impacting vulnerable populations. Confronting these challenges necessitates integrated solutions encouraging green, inclusive, and resilient urban growth. Green infrastructure, a nature-based solution, has emerged as a key strategy for enhancing cities' climate resilience while delivering multiple social, ecological, and economic benefits. This thesis investigates green infrastructure planning to optimize ecosystem services and its benefits for urban communities. Using the municipality of Sorocaba as a case study, the main objective was to develop a spatial model to identify priority areas for implementing green infrastructure, addressing themes like biodiversity, flood mitigation, temperature regulation, and social wellbeing. Additionally, the thesis aimed to explore urban planning scenario simulations, examining plausible futures for 2030 and 2050. The research hypothesis posits that spatial modeling can pinpoint priority areas by integrating natural and social systems amid the complexities of urban environments. The results highlight spatial trade-offs and synergies in identifying priority areas for urban multi-ecosystem services, emphasizing the importance of a well-connected green infrastructure network to enhance its multifunctionality and promote equitable access to green spaces, especially in areas with socio-spatial inequalities. The research also analyzed future urban growth scenarios, demonstrating how compact urban planning can mitigate the negative effects of unchecked sprawl and strengthen urban resilience, promoting sustainability, inclusion, and environmental justice.
Resiliência da paisagem urbana: integração de áreas naturais com o planejamento urbano
Keywords: Multicriteria Evaluation; Urban Ecosystem Services; Green Infrastructure; Future Scenarios; Urban Planning; GIS; Cellular Automata Algorithms; Urban Resilience; Climate Change; Impervious Surface; Atlantic Forest Biome; Google Earth Engine; Land Use and Land Cover; Land Surface Temperature; Southeast Brazil; Avaliação Multicriterial; Serviços Ecossistêmicos Urbanos; Infraestrutura Verde; Cenários Futuros; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL::TECNICAS DE PLANEJAMENTO E PROJETO URBANOS E REGIONAIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL